Identifying nursing documentation patterns associated with patient deterioration and recovery from deterioration in critical and acute care settings. (September 2021) - Schnock, Kumiko O.; Kang, Min-Jeoung; Rossetti, Sarah Collins; Garcia, Jose; Lowenthal, Graham; Knaplund, Chris; Chang, Frank; Albers, David; Korach, Tom Z.; Zhou, Li; Klann, Jeffrey G.; Cato, Kenrick; et al.
Abstract: Objectives: Nursing documentation behavior within electronic health records may reflect a nurse's concern about a patient and can be used to predict patient deterioration. Our study objectives were to quantify variations in nursing documentation patterns, confirm those patterns and variations with clinicians, and identify which patterns indicate patient deterioration and recovery from clinical deterioration events in the critical and acute care settings. Methods: We collected patient data from electronic health records and conducted a regression analysis to identify different nursing documentation patterns associated with patient outcomes resulting from clinical deterioration events in the intensive care unit (ICU) and acute care unit (ACU). The primary outcome measures were whether patients were discharged alive from the hospital or expired during their hospital encounter. Secondary outcome measures were clinical deterioration events. Results: In the ICU, the increased documentation of heart rate, body temperature, and withheld medication administrations were significantly associated with inpatient mortality. In the ACU, the documentation of blood pressure, respiratory rate with comments, singular vital signs, and withheld medications were significantly related to inpatient mortality. In contrast, the documentation of heart rate and "as needed" medication administrations were significantly associated with patient survival to discharge in the ACU. Conclusion: We successfully identified and confirmed the clinical relevancy of the nursing documentation patterns indicative of patient deterioration and recovery from clinical deterioration events in both the ICU and ACU.